Perception Differences in Violence against Child - Ahsen Kaya; Ekin O Aktas (Medicine Science, 2014)
Objectives: Mostly, people who apply violence do not realize the effects of it, especially child victims give strong emotional responses to violence. Behaviors without any intention of abuse or neglect can mostly be seen among the people, who are dealing with children intensely like teachers and parents. Aim of this work is to determine the perception differences of parents, teachers and children in violence. Methods: Revised form of Childhood Trauma Questionnaire and also 17 parameters related to violence were applied to children, parents and teachers and then their answers were compared with each other. Results: Questionnaires were responded by 411 children, 135 parents and 85 teachers. In each three groups, it was noticed that the ratio of perception of violence in parameters related to physical violence was higher than in parameters related to emotional violence. While the teachers had the highest perception of violence, children had the lowest perception of violence. Conclusions: Sensitiveness in perception of violence and education on this subject are not enough to stop violence. It must be prevented to apply violence in society for an aim of discipline and education and violence must not be seen as a way of teaching good manners. It also must not be applied as a tool for solving problems, gaining power and control. The rights of violence victims, especially children’s rights must be protected and there must be intimidating sanctions for people who practice violence on the others. [Med-Science 2014; 3(2.000): 1183-97]